Astaxanthin Prevents a Decrease of Hemopoietic Activity in Head and Neck Cancer Patients Receiving Cisplatin Chemotherapy (Randomized Controlled Trial) - Aminullah, Yusuf; Subagio, Hertanto Wahyu; Santosa, Damai; Naftali, Zulfikar (Migration Letters, 2024)
Decreased hemopoietic activity due to reactive oxygen species (ROS) in patients with head and neck cancer (HNC) can cause myelosuppression due to the side effects of cisplatin chemotherapy. External antioxidants, including astaxanthin, are needed to neutralize and fight ROS, preventing a decrease in hemopoietic activity. This study aims to prove and analyze the antioxidant effect of astaxanthin in preventing a decrease in hemopoietic activity through increasing levels of superoxide dismutase (SOD) and decreasing levels of malondialdehyde (MDA) in head and neck cancer patients due to cisplatin. The study design was an experimental randomized controlled trial pre-post test design with 42 research subjects randomly divided into two groups. The treatment group was given astaxanthin 2x4 mg, and the control group was given a vitamin C 1x500 mg and vitamin E 1x250 IU. Data analysis was performed by the Descriptive, Levene, Shapiro-Wilks, Wilcoxon, and Mann-Whitney tests. The results of this study stated, 42 study subjects met the inclusion criteria, most aged 41-50 years were 16 people (38.1%), male and female 2:1, Nasopharyngeal cancer 22 people (52.4%), stage IV 32 people (76.2%), Eastern Cooperative Oncological Group (ECOG) I 31 people (73.8%) and Normal Body Mass Index (BMI) 30 people (71.4%). There were significant differences in hemoglobin levels (p=0.012), erythrocyte counts (p=0.004), leukocyte counts (p=0.009), and MDA levels (p=0.014), while thrombocyte counts (p=0.178) and SOD levels (p=0.489)) was not significantly different. Supplementation of astaxanthin 2x4 mg for three weeks in head and neck cancer patients can prevent a decrease in hemopoietic activity (hemoglobin levels, erythrocytes, and leukocytes counts) by reducing malondialdehyde (MDA) levels in head and neck cancer patients receiving cisplatin.